PENERAPAN ANALISIS KORELASI KANONIK PADA HUBUNGAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH - PRABAWA, KADEK ANDREI; SUCIPTAWATI, NI LUH PUTU; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 6 No 1 (2017)DO - 10.24843/MTK.2017.v06.i01.p152, 2017)
Customer satisfaction is determined by the quality of customer service desired. Service quality of a company are important viewed from a consumer standpoint. The p